Incident Stroke and Its Influencing Factors in Patients With Type 2 Diabetes Mellitus and/or Hypertension: A Prospective Cohort Study - Wei-Wei Chang; Shi-Zao Fei; Na Pan; Ying-Shui Yao; Ying-Shui Yao; Yue-Long Jin (Frontiers in Cardiovascular Medicine, 2022)
ObjectiveTo understand the incidence of stroke in patients with type 2 diabetes mellitus (T2DM) and/or hypertension (HTN), and provide a basis for the prevention of stroke in these patients.MethodsA prospective cohort study was performed for adults with T2DM and/or HTN. The follow-up period was 1 year. The incidence and recurrence rate of stroke was calculated and a multivariate Cox proportional hazard was used to analyze influencing factors of stroke occurrence and recurrence in the follow-up of patients with T2DM and/or HTN.ResultsOf the 1,650 patients with T2DM and/or HTN, 1,213 patients had no history of stroke. After 1 year of follow-up, 147 new stroke cases occurred, and the incidence rate of stroke was 12.1%. Among the patients who had stroke history (413), there were 116 cases of stroke with a recurrence rate of 26.5%. Seven risk factors were independently associated with stroke occurrence among patients without stroke history, included smoking, abnormal total cholesterol abnormal low-density lipoprotein patients with comorbid T2DM with HTN, physical inactivity, carotid artery stenosis (CAS), and higher scores of National Institutes of Health Stroke Scale (NIHSS). Higher scores of NHISS and CAS were independent risk factors for the recurrence of stroke among patients with stroke history.ConclusionsPatients with T2DM and/or HTN have a higher rate of new stroke and recurrence after 1-year follow-up. Actively identifying the controllable risk factors, such as smoking and physical inactivity, will help reduce the risk of stroke and recurrence in patients with T2DM and HTN.